Gillnet selectivity for non‐targeted shark species in temperate Australia. (19th May 2022) - Braccini, Matías; Hesp, Alex; Walker, Terence I.
Abstract: The use of size‐selective fishing gear has been fundamental for the successful management of shark populations. For the main Australian shark fisheries, available data sets on gillnet selectivity experiments conducted since the 1990s were used to estimate gillnet selectivity parameters for nine commonly caught non‐target species: broadnose, draughtboard, Port Jackson and school sharks, common and southern sawsharks, smooth hammerhead and spikey and whitespotted dogfish. Size at selection increased with mesh size, but it varied with species, with some species having broader selectivity curves due to their particular morphological features. In particular, smooth hammerhead had much broader selectivity curves and larger length at maximum selection than other species of comparable size such as the broadnose shark. The selectivity curves derived in this study will allow a more accurate interpretation of catch size composition and model‐based assessments of stock status of these species